Perfil metabólico e reprodutivo de ratas obesas tratadas com Syzygium cumini (L.) Skeels - VALE, Caroline Castro (2016)
Metabolic syndrome (MS) is defined as a set of interrelated risk factors that contribute to type 2 diabetes mellitus (T2DM) and cardiovascular disease (CVD). SM also causes harmful effects on the reproductive system, especially for women, as it reducies ovulatory rates, increasies the number of abortions and late pregnancy complications, which increase the risk of infertility. As a form of treatment approaches are adopted both non-pharmacologic and pharmacologic. In this context, the use of alternative therapies with natural products has emerged as a safer and less associated with worsening of MS risk factors. Syzygium cumini (jambolan) is a species of Asian origin, but cultivated and used throughout the world for its anti-hyperglycemic, anti-hiperlipemiantes and antioxidants. Through these actions, we sought to investigate whether the hydroalcoholic extract of the leaves of S. cumini (EHSyz) improves the metabolic changes and consequently, changes in reproductive function in rats with induced obesity L-monosodium glutamate (MSG) a dose 4g/Kg/day. Wistar female rats were divided into the following groups: CTRL group (treated with NaCl 0.9% 0.1 ml / 100g / day v.o,); MSG group (treated with NaCl 0.9% 0.1 ml / 100g / day V.O.); EHSyz obese group (treated with EHSyz at a dose of 500mg / kg / day, V.O.), each for 60 days. The administration EHSyz promoted with retention of weight gain, reduction Lee index and improved glycolipid profile, with reduced serum triglyceride levels by 60.7% and 29.7% compared to cholesterol total.O EHSyz even avoided introduction resistance table in the treated rats. However, despite the improvement in oligociclicidade, the extract was not able to improve reproductive impairment of the treated rats. Thus, we conclude that treatment with EHSyz produced marked effects on metabolic parameters in obese rats without interfering with the reproductive capacity of the same.